Maturação da via auditiva e aquisição da linguagem em crianças nascidas pré-termo tardio e a termo com e sem risco psíquico - Rechia, Inaê Costa (2016)
This thesis aimed to evaluate the possible relationship between maturation of the auditory pathway, language acquisition and the presence of psychological risk in preterm infants and term. It was also analyzed the possible relationship between maturation of the auditory pathway and language acquisition in late preterm infants and term to describe auditory pathway maturation patterns of these babies, analyze the possible relationship between maturation of the auditory pathway and psychological risk. This is a cohort study, longitudinal, in which linked variables were compared to hearing and language of 0-12 babies. The research population was composed of late preterm infants and term without neurological injury or obvious organic syndrome. The sample consisted of 54 babies, being 17 babies from the late preterm group and 37 babies from the group born at term from the study 2, and 31 babies composed the no risk group and 23 babies with psychic risk from study 3. The families went through initial and continuing interviews to collect data on pregnancy, birth, food, among others. Hearing maturation was assessed by analysis of Cortical Auditory Evoked Potentials in the first, sixth and twelfth month. The gathering sessions were filmed at 3, 6, 9 and 12 months for analysis and checking of some of the protocols used. To verify the psychological risk, evaluations were conducted using IRDIS and PRÈAUT questiionnaries. To verify the language acquisition, evaluations used Language Acquisition Enunciation Sign, DENVER II and Vocabulary Checklist. All aspects were evaluated on the day of collection and subsequently confirmed by the filming. Analyzing the evaluations, it was found that in all groups there was a statistically significant hearing maturation. Preterm babies showed greater maturity than those born at term, due to its higher latency at birth and at 6 months. In the evaluation of 12 months, it was observed equivalent results. As for the language, it was observed that late preterm infants had lower performance in DENVER II in Phase 4. Regarding the Language Acquisition Enunciation Sign, which evaluates the mother-infant interaction, in Phase 1 there wasn't statistically significant difference between the groups in favor of the group born at term as expected. As for the test Vocabulary Checklist, it was observed that the term infants showed better understanding of vocabulary at 12 months. Analyzing the auditory maturation and psychological risk, infants with greater psychological risk also had higher latencies. In this sample, there was a higher concentration of risk with babies in Phase I of IRDlS (42.59%, n = 23) and lower concentrations in Phase IV (14.81%, n = 8). In assessing the PRÈAUT at 4 months, 42.59% (n = 23) of the babies were at risk and 9 months only 20.37% (n = 11). Finally, there is the importance for clinical practice, the auditory maturation of monitoring and the development of listening skills of children who show biohazardous and / or environmental risk, such as prematurity, especially extreme cases, as well as the psychic risk.